The Right to Express Opinion through Writing and Publishing in the Kuwaiti Constitution - Almurshid, Razan; Badran, Semon (Journal of Legal Sciences, 2026)
The definition of "freedom" cannot be abstract; its value is determined by its connection to public and private, individual, and societal behaviors, whether social or political in nature. In our discussion, we will focus on freedom of expression in writing and publishing, and the various means and methods associated with this issue.Legislators are largely influenced by ethical philosophy when formulating laws governing society, particularly concerning freedom of expression, which is fundamental to democratic societies and requires legal and practical guarantees to be exercised freely. Through these guarantees, "freedom of expression" becomes a means to counter despotism and a form of oversight over the actions of authorities and governments. Thus, freedom of expression is essential to any state system and a significant achievement for advanced societies and respected governments.Among the most crucial freedoms for preserving human rights and achieving democratic order is enabling "freedom of the press" as the fourth authority in the state. Therefore, the Kuwaiti constitution and international charters on freedoms, such as freedom of belief, education, opinion, scientific research, assembly, and association, play a vital role.The Kuwaiti constitution is credited with guaranteeing economic and social rights and the freedom of expression through writing and publishing as a means to build and activate the democratic system. However, democracy is not possible without the sovereignty of the constitution as the basis for the nation's sovereignty. Hence, it does not evolve and solidify without scrutiny of the constitutionality of laws, leading to the need for judicial review of laws' constitutionality. From this perspective, democracy is a general legal need and a specific social necessity because it directly affects individual freedoms and results from pure ideas and significant popular, social, and political efforts.The Kuwaiti constitution is credited with preserving the economic and social rights of individuals and freedom of opinion through writing and publishing, as one of the means of building and activating the democratic system.In the research, we will discuss the foundations, rights, and types of intellectual freedoms guaranteed by the constitution, their relationship to the democratic system, and their impact on the right to express opinion through writing and publishing.